Understanding Memory Triggers for Task Tracking - Brush, A.J.; Meyers, Brian; Tan, Desney; Czerwinski, Mary (Extended Abstracts at CHI 2007 Conference on Human Factors in Computing Systems, 2007)
Software can now track which computer applications and documents you use. This provides us with the potential to help end-users recall past activities for tasks such as status reporting. We describe findings from field observations of eight participants writing their status reports. We observed interesting trends, including the reliance on memory triggers, which were either retrieved from explicit self-reminders, from implicit breadcrumbs left while performing their tasks or directly from memory. Participants perceived spending relatively short amounts of time composing their status reports, suggesting that any technology solution must offer dramatic improvements over current practice.